The follow-up of myocardial injury and left ventricular function after spontaneous coronary artery dissection - Krljanac, Gordana; Apostolovic, Svetlana; Polovina, Marija; Maksimovic, Ruzica; Nedeljkovic Arsenovic, Olga; Djordjevic, Nemanja; Stankovic, Stefan; Savic, Lidija; Djokovic, Aleksandra; Viduljevic, Mihajlo; Stankovic, Sanja; Asanin, Milika (Frontiers in Cardiovascular Medicine, 2023)
Monitoring patients with spontaneous coronary dissection (SCAD) is a critical segment in their care, as no accepted recommendations about that. To this end, finding clinical or imaging predictors of recurrent events in these patients is essential for both predicting adverse events and guiding treatment decisions between conservative medical therapy and percutaneous coronary intervention. Myocardial 2 This is a provisional file, not the final typeset article injury and left ventricular function after SCAD can be variable parameters that require monitoring.Echocardiography and cardiac magnetic resonance are two useful imaging techniques to do so. This review aims to analyze previously published results on the monitoring of myocardial injury and left ventricular function in SCAD patients, while also highlighting the potential benefits provided by contemporary imaging techniques that could further improve patient care going forward.